Dimensions of marital satisfaction in the days of Corona: a qualitative study - Motahari Nasab, Akram; Farahbakhsh, Kiumars; Borjali, Ahmad; Farokhi, Norali (Applied Family Therapy Journal (AFTJ), 2022)
Aim: Considering the importance of couples’ relationships in the family, this study was conducted to develop a pattern of marital satisfaction during the corona period. Methods: This qualitative study was conducted on the basis of data theory. In this stage, the researcher has identified the constructive components in marital satisfaction during the corona period and compared the two groups with marital satisfaction and marital dissatisfaction. For this reason, Enrich’s marital satisfaction questionnaire was filled by women between 55-25 years old who were married and had children 13-6 years old. At this stage, the sampling method was purposeful and available. Among them, 12 subjects with low marital satisfaction and 12 people who had good marital satisfaction were selected and interviewed. Axial coding method was used to analyze the interview data. The codes were confirmed by 10 professors and finally comparisons were made between the two groups and a conceptual model was developed. Results: The results of this study showed that the main factors affecting marital satisfaction during the coronavirus outbreak include eight cases of love (empathy, affection, appreciation, sexual satisfaction, mutual understanding and caring about the wishes of the spouse), border management (fairness in the division of duties, management of family involvement and independence, creating the privacy of children and parents, providing emotional needs of parents and supporting and assisting parents), family work balance (flexibility in role ( taking responsibility for things, and prioritizing the family against working outside), secure attachment (trusting in your abilities, having a positive view of your spouse and balancing intimacy and personal independence), emotional maturity (keeping the child alive, flexibility and limiting the involvement of families), religious beliefs (belief in trust in God, transient and temporary suffering, cooperation in the service of charity and good service). Attending religious ceremonies in accordance with protocols, problem solving (contentment, dialogue, resolving misunderstandings, consulting and getting help from external sources of support) and time management (using cyberspace for personal affairs, two-person recreation between husband and wife, having leisure time for yourself and taking time for family fun). Conclusion: The results help counseling centers to gain a broad view of women’s problems during quarantine and in crisis and help them to better adapt to a crisis such as corona and increase the intimacy of couples between them and their spouses.